Impact of training needs analysis on organizational effectiveness among construction companies in Saudi Arabia - Albassami, Ahmad Mohmad (2021)
Training is crucial in Saudi Arabia. Saudization plans emphasize training because of its effect on the construction business. With this approach, the government exacerbated the labor shortage, reducing the organization's efficiency. The other Gulf nations face a similar situation where a lack of construction machinery operators forces certain enterprises to rent machines with an operator. The demand for training becomes a burden in the companies. Furthermore, training is often inadequate due to employees' inexperience or a language barrier. Most training in KSA is ineffective owing to trainers' lack of cultural knowledge. Therefore, the trainer uses insignificant input and reduces training effectiveness. There is limited research on training needs analysis (TNA) and the benefit of training for organizational success in the Arab world, especially in Saudi Arabia. Moreover, limited study links TNA and organizational effectiveness to the construction industry. Thus, the present research intends to investigate TNA in Saudi building construction success. The study is not restricted to a specific organization's size, although its size controls the link between TNA and perceived training value. Moreover, additional variables for training include consulted trainer and training quantity, and both received minimal investigation. The current study uses consulting trainers to assess perceived training efficacy. Given the above scenario, the study seeks to delineate the relationship between the TNA approach and organizational effectiveness in the construction sectors of Saudi Arabia. The study employs four hundred and sixty-one (461) small, medium and large companies in the construction industry in KSA. The research uses a questionnaire to collect the data for the study, and Partial Least Square Structural Equation Modelling (PLS-SEM) analyzes the collected data. The findings show a substantial positive relationship between TNA and perceived training utility as stated in objective one. The study suggests that TNA affects the perceived value of training, and the data correlates with objective two but has no significant correlation with training quantity and perceived value. Perceived training utility correlates positively with organizational effectiveness. It implies that training utility as training efficacy influenced the perceived value of the construction firm's effectiveness. Objective four shows a moderate effect of organizational size on the link between TNA and the perceived utility of training. Given the study's findings, construction companies in Saudi Arabia organize extensive training needs analyses to improve the perceived value of training. The current study shows that training hours should benefit the employee. Training duration is not as crucial as training need analysis for Saudi construction companies. Similarly, larger firms use training more effectively than smaller ones. Small construction enterprises in Saudi Arabia need to grow to improve training and organizational performance. The current study proves that perception of organizational support strengthens the TNA and training usefulness relationship. Thus, top management in KSA construction businesses should promote training to show their commitment to staff development.